A meta-analysis of the role of trust in the leadership- performance relationship. Issue 1 (2nd January 2021) - Legood, Alison; van der Werff, Lisa; Lee, Allan; Den Hartog, Deanne
ABSTRACT: Trust plays a critical role as a key mechanism through which the positive impact of leadership can be elicited. This meta-analysis examines the incremental validity of eight leadership styles (transformational, transactional, authentic, ethical, servant, abusive, paternalistic and empowering) in predicting affective and cognitive dimensions of trust as mediating mechanisms in the relationship between leadership and performance outcomes. To counter issues of common method variance, we focus on the impact these mediated relationships have on independently measured other ratings of outcomes; task performance and organizational citizenship behaviour (OCB). We also test whether trust in the leader differs from that of the broader construct of Leader-Member Exchange (LMX) quality. Using 185 independent studies conducted since 1988, we find that contemporary styles, particularly servant and ethical leadership, demonstrate incremental validity over transformational and transactional (contingent reward) leadership in predicting trust in the leader. Meta analytical mediation tests reveal that trust in the leader and LMX play unique roles in mediating the relationship between leadership styles and performance related outcomes. Finally, evidence suggests that affective and cognitive dimensions of trust play a differential role in this mediating process and that affective trust in the leader is a more powerful predictor of performance and OCB.